Return to work after severe traumatic brain injury: a national study with a one-year follow-up of neurocognitive and behavioural outcomes. Issue 2 (7th February 2020) - Sigurdardottir, Solrun; Andelic, Nada; Wehling, Eike; Anke, Audny; Skandsen, Toril; Holthe, Oyvor Oistensen; Manskow, Unn Sollid; Roe, Cecilie
ABSTRACT: The objectives were to investigate the frequency of return-to-work (RTW) one year after severe traumatic brain injury (sTBI: Glasgow Coma Scale, GCS 3–8) and to identify which demographic and injury-related characteristics and neurocognitive factors are associated with RTW. This study is part of a prospective national study on sTBI conducted in all four Norwegian Trauma Referral Centres, including patients aged >15 years over a period of three years ( n  = 378). For the purpose of this study, only pre-employed individuals of working age (16 to 67 years) were investigated for RTW ( n  = 143), and of these, 104 participants underwent neuropsychological testing. Measures of acute injury severity, neuropsychological composite scores (Memory, Processing Speed, Executive Functions) at the one-year follow-up, and the Behaviour Rating Inventory of Executive Functions (patient- and relative reports) were explored as predictors of RTW. The frequency of RTW was 54.5%. Multivariate logistic regression analyses identified younger age, shorter length of stay in intensive care, better Processing Speed scores, and lower levels of metacognitive difficulties as rated by relatives as significant predictors of RTW. Findings support the importance of neuropsychological measures in predicting long-term RTW and highlight the need to address neurocognitive and behavioural difficulties to improve RTW after sTBI.